Determinants of low birth weight among newborns delivered in China: a prospective nested case-control study in a mother and infant cohort - Zhuomin Huang; Quanfu Zhang; Litong Zhu; Haishan Xiang; Depeng Zhao; Jilong Yao (Taylor & Francis Group, 2023)
This nested case-control study aimed to investigate the determinants of low birth weight among newborn babies delivered in Shenzhen, Guangdong, China. We recorded socio-demographic data, health status before pregnancy, pregnancy outcomes and complications in a Shenzhen mother and infant cohort. Among 8951 cases, 401 (4.48%) had low birth weight and 1.65% were full-term with LBW. Maternal body mass index, family income, history of pregnancy, hypertension before pregnancy, vaginal bleeding in 1st trimester, pregnancy-related diabetes, hypertension, placenta previa, placental abruption, premature rupture of membrane, oligohydramnios, and placental types were significantly associated with low birth weight (P < 0.05). In this study, high-risk and mainly preventable factors were linked to low birth weight. Adequate antenatal care, proper maternal nutrition and implementation of proven strategies to prevent high-risk factors may be effective ways to reduce the incidence of low birth weight.